Optogenetic induction of cortical spreading depression in anesthetized and freely behaving mice - Houben, Thijs; Loonen, Inge Cm; Baca, Serapio M; Schenke, Maarten; Meijer, Johanna H; Ferrari, Michel D; Terwindt, Gisela M; Voskuyl, Rob A; Charles, Andrew; van den Maagdenberg, Arn Mjm; Tolner, Else A (Journal of cerebral blood flow and metabolism, 2017)
Cortical spreading depression, which plays an important role in multiple neurological disorders, has been studied primarily with experimental models that use highly invasive methods. We developed a relatively non-invasive optogenetic model to induce cortical spreading depression by transcranial stimulation of channelrhodopsin-2 ion channels expressed in cortical layer 5 neurons. Light-evoked cortical spreading depression in anesthetized and freely behaving mice was studied with intracortical DC-potentials, multi-unit activity and/or non-invasive laser Doppler flowmetry, and optical intrinsic signal imaging. In anesthetized mice, cortical spreading depression induction thresholds and propagation rates were similar for invasive (DC-potential) and non-invasive (laser Doppler flowmetry) recording paradigms. Cortical spreading depression-related vascular and parenchymal optical intrinsic signal changes were similar to those evoked with KCl. In freely behaving mice, DC-potential and multi-unit activity recordings combined with laser Doppler flowmetry revealed cortical spreading depression characteristics comparable to those under anesthesia, except for a shorter cortical spreading depression duration. Cortical spreading depression resulted in a short increase followed by prolonged reduction of spontaneous active behavior. Motor function, as assessed by wire grip tests, was transiently and unilaterally suppressed following a cortical spreading depression. Optogenetic cortical spreading depression induction has significant advantages over current models in that multiple cortical spreading depression events can be elicited in a non-invasive and cell type-selective fashion.